Upaya Peningkatan Pengetahuan Terkait Beyond Use Date (BUD) Obat di SMA Negeri 5 Samarinda - Rija’I, Hifdzur Rashif; Maulana, Muhammad Rajab Fathin; Rizqullah, Muhammad Azril (Jurnal Pelayanan dan Pengabdian Kesehatan untuk Masyarakat, 2025)
Beyond Use Date (BUD) is a term that refers to the date on which a pharmaceutical product or drug preparation is considered no longer safe or effective for use. Until now, the general public has only been familiar with ED compared to BUD, and the inclusion of Beyond Use Date on drug labels is still very minimal, resulting in a lack of knowledge about BUD among the public. The purpose of this activity is to increase the knowledge of students in class X-10 at SMA Negeri 5 Samarinda regarding the Beyond Use Date (BUD) of drugs. The health promotion activity used PowerPoint and leaflets as media. The activity began with a pre-test using Quizizz, followed by a presentation of the material, a question and answer session, and a post-test using Quizizz. This activity was attended by 31 participants. The results of the health promotion activity in class X-10 of SMA Negeri 5 Samarinda were an average pre-test score of 37.42% and an average post-test score of 82.58%. The question that could be answered correctly in the pre-test was question 4, with a score of 77.42%. Meanwhile, the questions that could be answered correctly in the post-test were questions 1, 2, 3, and 4, with 90.32%, 74.2%, 87.1%, and 93.55% respectively. The conclusion of this activity is that there was an increase in knowledge related to the Beyond Use Date (BUD) of medicines among students in class X- 10 at SMA Negeri 5 Samarinda.